Optimized Balance Between Electricity Load and Wind-Solar Energy Production - Guozden, Tomás; Carbajal, Juan Pablo; Bianchi, Emilio; Solarte, Andrés (Frontiers in Energy Research, 2020)
One of the greatest obstacles in the exploitation of wind and solar resources is the uncertainty in their availability, usually known as intermittence. These effects can be greatly diminished by combining wind and solar resources from different locations. In this article we propose a numerical optimization of future renewable capacity additions aimed to minimize the dispersion of the residual power, which is the remaining electricity load after subtracting the contribution of renewables. Results show that penetration of wind and solar power may increase in another 10% of energy share while keeping the dispersion of the residual power constant, by adding capacity at sites most positively correlated with electricity load. For further increments, an optimized distribution of wind and solar facilities compensates variations between renewables. In this situation, wind sites that anticorrelate with solar cycle play an important role.